Spatial distribution and formation of corrosion products in relation to zinc release for zinc sheet and coated pre‐weathered zinc at an urban and a marine atmospheric condition. Issue 4 (7th December 2011) - Hedberg, J.; Le Bozec, N.; Wallinder, I. Odnevall
Abstract Zinc release data from 5 years of unsheltered exposures in a marine and an urban site is compiled for different zinc material types. The thin surface treatment on zinc materials is gradually detached after approximately 2 years at both sites, revealing the pre‐weathered zinc surface unprotected. This consequently increased the release rates of zinc from this surface, whereas the zinc runoff rate from the bare zinc sheet remained relatively stable. Raman studies on bare zinc sheet exposed for 5 years at the marine site revealed zinc oxide of varying crystalline nature and hydrozincite to appear localized and separated from each other.